Fabrication, characterization and micromechanics modeling of the electrical conductivity of reduced graphene oxide/aramid nanofiber nanocomposites. (2nd August 2019) - Zhou, Tianyang; Boyd, James G; Loufakis, Dimitrios; Lutkenhaus, Jodie L; Lagoudas, Dimitris C
Abstract: Graphene-based materials with high graphene concentration are of great interest for multifunctional, structural electrode materials that simultaneously store electrical energy and carry structural loads. Graphene-based materials can have a high electrochemically active surface area, high electrical conductivity, and good stiffness and strength. Published analytical studies of electrical conductivity are mostly focused on graphene-based polymer nanocomposites with very low concentrations of conductive fillers, for percolation purposes. In the research reported herein, reduced graphene oxide (rGO) and aramid nanofiber (ANF) nanocomposite films with higher concentrations of rGO, up to 100 wt% rGO, were fabricated and characterized for their electrical conductivity. In addition, a hybrid micromechanical and phenomenological model of electrical conductivity was developed to include the effects of rGO waviness and conductivity, volume fraction of ANF, random orientation of rGO and ANFs, interphase thickness and interphase conductivity. The experimentally measured in-plane conductivity of rGO/ANF nanocomposite films decreases exponentially with the addition of ANFs. For example, the experimental in-plane conductivity of rGO/ANF nanocomposite films was increased 30-fold by decreasing the ANF loading from 25 wt% to 0 wt%. This exponential relationship can be explained by the model proposed. The model showed that the influence of the interphase thickness and interphase conductivity was more significant than that of waviness. The effective in-plane conductivity changed by 20% when the waviness was decreased from maximum observed value to minimum. The effective in-plane conductivity decreased by two orders of magnitude when the interphase thickness was changed from 0 to 0.5 nm and the interphase conductivity was 0.09 S m −1 . The model results agreed with the experimental data when the interphase thickness and conductivity vary with the volume fraction of rGO. The addition of ANFs is significant due to the influence it has on the microstructure of the composite and the interphase structure and conductivity. This model can be used for composites with coated fibers or continuous polymeric matrix by adjusting the interphase morphology.